2015
DOI: 10.1242/jeb.118562
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic sensing and behavior by oyster larvae in turbulence and waves

Abstract: Hydrodynamic signals from turbulence and waves may provide marine invertebrate larvae with behavioral cues that affect the pathways and energetic costs of larval delivery to adult habitats. Oysters (Crassostrea virginica) live in sheltered estuaries with strong turbulence and small waves, but their larvae can be transported into coastal waters with large waves. These contrasting environments have different ranges of hydrodynamic signals, because turbulence generally produces higher spatial velocity gradients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
76
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 86 publications
(105 reference statements)
1
76
2
Order By: Relevance
“…Various studies highlight that larvae actively respond to turbulence or components of turbulence, e.g., larval boat snails Crepidula fornicata increase upward swimming with increasing turbulence level [67], larval sea slugs Phestilla sibogae retract their vela when encountering turbulent filaments containing chemical cues [48], and larval eastern oysters Crassostrea virginica dive when experiencing high fluid acceleration over short time intervals [29]. Together with other modeling studies, these earlier works suggest turbulence enhances larval settlement [68,56] (but see [69], who suggested that an increase in turbulence reduces settlement in scallop larvae). Recently, deformation associated with horizontal shear has been suggested to induce competency in larval urchins [70] and to induce cloning in coral larvae [71].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Various studies highlight that larvae actively respond to turbulence or components of turbulence, e.g., larval boat snails Crepidula fornicata increase upward swimming with increasing turbulence level [67], larval sea slugs Phestilla sibogae retract their vela when encountering turbulent filaments containing chemical cues [48], and larval eastern oysters Crassostrea virginica dive when experiencing high fluid acceleration over short time intervals [29]. Together with other modeling studies, these earlier works suggest turbulence enhances larval settlement [68,56] (but see [69], who suggested that an increase in turbulence reduces settlement in scallop larvae). Recently, deformation associated with horizontal shear has been suggested to induce competency in larval urchins [70] and to induce cloning in coral larvae [71].…”
Section: Introductionmentioning
confidence: 76%
“…In the water column, strong swimming larvae such as crab zoea actively change their swimming speeds in response to turbulence intensity [54] and barnacle cyprids swim upwards to counteract downwelling currents [55]. For moderate swimming larvae such as oyster larvae, a plasticity in response to turbulence has been observed, where competentto-settle larvae have been observed both to sink [27] and swim upward [56,28] in high turbulence; these active behavioral responses may be regulated by body size. For weaker swimming plankton, such as larval sand dollars, it has been observed that their morphologies primarily interact passively with ambient flow [57,46].…”
Section: Introductionmentioning
confidence: 99%
“…Couette flow produces high strain rates and vorticity, whereas solid-body rotation produces negligible strain and constant vorticity. Rotating flows unavoidably produce centripetal acceleration, but here the accelerations were lower than those that previously induced larvae to dive in rectilinear wave motions (Fuchs et al, 2015). Each device was operated in two different orientations, one with its axis horizontal and one with its axis vertical (Figs 2,3).…”
Section: Introductionmentioning
confidence: 80%
“…1). Oyster larvae respond to both turbulence and waves by either swimming faster upward or diving actively downward (Fuchs et al, , 2015. In waves, these responses are elicited by high accelerations, indicating that statocysts can function as accelerometers (Fuchs et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation